In-process grinding monitoring through acoustic emission - Aguiar, Paulo R. [UNESP]; Serni, Paulo J. A. [UNESP]; Dotto, Fábio R. L. [UNESP]; Bianchi, Eduardo C. [UNESP] (Springer Nature, 2006)
This work aims to investigate the efficiency of digital signal processing tools of acoustic emission signals in order to detect thermal damages in grinding processes. To accomplish such a goal, an experimental work was carried out for 15 runs in a surface grinding machine operating with an aluminum oxide grinding wheel and ABNT 1045 Steel as work material. The acoustic emission signals were acquired from a fixed sensor placed on the workpiece holder. A high sampling rate data acquisition system working at 2.5 MHz was used to collect the raw acoustic emission instead of the root mean square value usually employed. Many statistical analyses have shown to be effective to detect burn, such as the root mean square (RMS), correlation of the AE, constant false alarm rate (CFAR), ratio of power (ROP) and mean-value deviance (MVD). However, the CFAR, ROP, Kurtosis and correlation of the AE have been presented more sensitive than the RMS. Copyright © 2006 by ABCM.
Keywords: Acoustic emission; Burn detection; Electrical power; Grinding; Monitoring; Acoustic emission signals; Acoustic emissions; Acoustic signal processing; Alumina; Data acquisition; Digital signal processing; Grinding machines; Sampling; Statistical methods; Grinding (comminution)